Determining the Brand Loyalty of Bamboo Plywood Design of Thailand: Moderating Role of Sustainable Marketing - Boonsong, Ratchadaporn; Tungsinpoolperm, Sangsom; Chanplin, Panupong (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current study examined the role of innovative brand, company goodwill and brand uniqueness on customer satisfaction and brand loyalty. The objective of this study is to identify the determinants of brand loyalty. Consequently, the relationship between innovative brand, company goodwill, brand uniqueness, customer satisfaction, sustainable marketing and brand loyalty were examined. Population of the study was the companies related to the Bamboo plywood designing from Thailand. Respondents of the study was the employees of Bamboo plywood designing companies. Data collection was carried out through questionnaire and simple random sampling was carried out. Sample size of the study was 300 employees from Bamboo plywood designing companies. Results of the study revealed that innovative brand, company goodwill, brand uniqueness, customer satisfaction and brand loyalty have major role in brand loyalty. The determinants of brand loyalty are; innovative brand, company goodwill and brand uniqueness. Sustainable marketing also has positive effect on brand loyalty. Therefore, practitioners should promote brand loyalty in Bamboo plywood designing by promoting innovative brand, company goodwill, brand uniqueness and customer satisfaction.